Efficacy of physical layer preamble manipulation for IEEE 802.11a/ac. Issue 8 (1st April 2016) - Ramsey, B.; Fuller, J.; Badenhop, C.
Abstract : Wireless physical layer manipulation is a recently discovered technique for selective packet obfuscation. This process exploits the unique and proprietary nature of transceiver designs rather than manufacturing imperfections. To date, preamble manipulation has only successfully been demonstrated on low data rate transceivers operating in the 2.4 GHz band. This Letter investigates the effectiveness of preamble manipulation on common 5 GHz IEEE 802.11a and IEEE 802.11ac wireless transceivers for the first time. Herein it is demonstrated that the preamble short training sequence length can be manipulated to discern among the six transceiver designs under test with greater than 99% accuracy using fewer than 20 packets.